TANGGUNG JAWAB RUMAH PENYIMPANAN BENDA SITAAN NEGARA DALAM PENGELOLAAN BENDA SITAAN DAN BARANG RAMPASAN HASIL TINDAK PIDANA - Rachmatika Lestari; Nila Trisna; Dara Quthni Effida (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2020)
Article 44 of the KuHP states that: "Confiscated objects are stored in state confiscation houses. In Article 1 number 3 of Government Regulation No. 27 of 1983 on the Implementation of Criminal Events Act also mentions that the State Confiscation House is hereby called RUPBASAN is the place of objects confiscated by the State for the purposes of judicial proceedings. RUPBASAN is where objects confiscated by the State for the purposes of judicial proceedings. RUPBASAN is established in every capital city or city district, and if necessary can be established RUPBASAN Branch. However, in practice not all district capitals or cities have RUPBASAN to manage confiscated objects and loot proceeds from crimes, so the management of the proceeds of crime is under direct management by the law enforcement agencies that handle such crimes. Based on the background as described above, the formulation of the problems in this study is: what are the arrangements regarding the management of Confiscated Objects in the RUPBASAN? And how is the management of Confiscated Goods and Proceeds of Looting Crimes in Indonesia? This research is a normative juridical study, namely research conducted by examining library materials or secondary data. The results showed the amount of assets or items seized from the defendant in criminal cases by law enforcement officers that were still not properly managed, meaning they had been confiscated or taken from the defendant, but were not properly managed. So far there has been an institution called RUPBASAN, as stipulated in Law No. 8 of 1981 on KUHAP, PP No. 27/1983 on The Implementation of KUHAP, and Regulation of the Minister of Justice Number: M.05.UM.01.06 of 1983 on the Management of Confiscated Goods and State Booty in the State Confiscation House, but not utilized properly. Confiscated items are all stored in the police station or prosecutor's office, whereas if stored and left unmanaged properly then there will be a decrease in value. Keywords: responsibilities of the RUPBASAN, confiscation objects, proceeds of crime